Author Correction: Evaluating drug targets through human loss-of-function genetic variation (Nature, (2020), 581, 7809, (459-464), 10.1038/s41586-020-2267-z) - Minikel, Eric Vallabh (Nature Research, 2022)
10.1038/s41586-020-03177-5